Icariin inhibits chondrocyte apoptosis and angiogenesis by regulating the TDP‐43 signaling pathway. Issue 4 (7th February 2019) - Huang, He; Zhang, Zhao‐Fei; Qin, Feng‐Wei; Tang, Wang; Liu, Dong‐Hua; Wu, Pei‐Yu; Jiao, Feng
Abstract: Background: This study focused on the mechanisms where icariin inhibited chondrocyte apoptosis and angiogenesis by regulating the TDP‐43 signaling pathway. Methods: A rat osteoarthritis (OA) model was established by collagenase injection. Histological examination of the articular cartilage and synovial tissue was performed 6 weeks after operation. Cartilage cell line overexpressing TDP‐43 and mesenchymal stem cell line (TDP43‐MSCs) of the rat TDP43 gene were established. Results: In OA rats transplanted with TDP43‐mMSCs, TDP43 was highly expressed in chondrocytes (TDP43‐HC), while TDP43 expression was low in HC and MSCs‐HC ( p < 0.05). After the intervention of MSCs‐TDP43, high expression of TDP43 induced the apoptosis and death of chondrocytes. After the addition of icariin, late apoptosis and death of TDP43‐HC were significantly attenuated. Apoptosis and death of HC, MSCs‐HC, and TDP43‐HC cells were effectively controlled with icariin, and no apparent cell death was found. ELISA showed that the VEGF and HIF‐1 alpha were significantly higher in the rat OA model than the normal control rats. Conclusion: TDP43‐MSC transplantation interfered with the expression of TDP43 in the articular chondrocytes of OA rats, which may impact on inducing apoptosis of chondrocytes as well as inhibiting the proliferation of chondrocytes. Additionally, TDP43‐MSCs appeared to promote the formation of neovascularization in the synovial tissue, which could be significantly attenuated by icariin. Abstract : TDP43‐MSCs transplantation interfered with the expression of TDP43 in the articular chondrocytes of OA model, which may have impact on inducing apoptosis of chondrocytes as well as inhibiting the proliferation of chondrocytes. Furthermore, TDP43‐MSCs have the effect of promoting the formation of new blood vessels in the synovial tissue of joints.